On Efficient Channel Modeling for Video Transmission over Cognitive Radio Networks - Hassan, Mohamed (2016)
This paper investigates the problem of video transmission over cognitive radio networks with the objective of maintaining continuous video playback while gracefully degrading the quality of the reconstructed video sequences, if needed. We focus on modeling the channel availability to secondary users, which is a major limiting factor on the continuity of the streaming process. A Markov chain model for the channels availability in an M-channels system is developed. This model is used to estimate the likelihood of transmission interruptions a secondary user might experience due to the loss of a channel to a primary user. We also propose a joint adaptive mechanism where a simple source rate control scheme is integrated with an adaptive playback approach to reduce the impact of channels relocation/unavailability on the streaming process of active secondary users. Simulations and numerical investigations demonstrate the correctness of the proposed channel model. Simulation results also indicate that instants of playback buffer starvation at the secondary user ends could be avoided only when the hybrid approach is employed.